MANAJEMEN PEMBENTUKAN BUDAYA RISET ( RESEARCH CULTURE) PADA SISWA MADRASAH ALIYAH NEGERI 2 KUDUS - Az Zafi, Ashif; Maula, Mahmudatul; Tsuroyya, Anis; Sari, Laura Ameylia Novita; Jauhari, Ahmad (Piwulang: Jurnal Pendidikan Agama Islam, 2024)
Abstract This article discusses the management of the formation of a research culture in MAN 2 Kudus students. The research is motivated by the lack of educational institutions that carry out research development. This research aims to determine the inclusion of research culture at Madrasah Aliyah Negeri 2 Kudus, the MAN 2 Kudus Research Curriculum, and the management of establishing a MAN 2 Kudus research culture for its students. This type of research, in analyzing data, uses a qualitative approach with interviews and observations, intended for the researcher to reveal and describe in depth. The results of the research show that the introduction of research culture at MAN 2 Kudus began with Mr. and Mrs. Teachers of MAN 2 Kudus after returning from their academic research development training activities. g getting research academic assignments in its own madrasah, MAN 2 Kudus formed a Research curriculum to regulate the development of research culture in students, MAN 2 Kudus carried out stage management in forming a research culture in MAN 2 Kudus students by including research in local content subjects. Abstrak Artikel ini membahas mengenai manajemen pembentukan budaya riset (Research Culture) pada siswa MAN 2 Kudus. Penelitian dilatarbelakangi oleh minimnya lembaga Pendidikan yang melakukan pengembangkan riset. Penelitian ini bertujuan untuk mengetahui masuknya budaya riset di Madrasah Aliyah Negeri 2 Kudus, Kurikulum Riset MAN 2 Kudus, dan manajemen pembentukan budaya riset MAN 2 Kudus bagi Siswanya. Jenis Penelitian ini dalam menngali data menggunakan pendekatan kualitatif dengan wawancara dan Observasi, dimaksudkan agar peneliti mengungkap dan mendeskripsikan secara mendalam Hasil Penelitian menunjukkan bahwa masuknya budaya riset di MAN 2 Kudus berawal dari  Bapak dan Ibu Guru MAN 2 Kudus  setelah pulang dari kegiatan pelatihan pengembangan akademik risetyan g mendapatkan tugas akedmik riset di madrasahnya sendiri, MAN 2 Kudus membentuk kurikulum Riset untuk mengatur perkembangan budaya penelitian pada siswa, MAN 2 Kudus melakukan manajemen tahapan tahapan dalam membentuk budaya riset pada siswa MAN 2 Kudus dengan memasukan Riset pada mata pelajaran muatan lokal. Keywords: Management, Research Culture, Students of Madrasah.